Onset and steady-operation features of low temperature differential multi-stage travelling wave thermoacoustic engines for low grade energy utilization. (15th November 2015) - Zhang, Xiaoqing; Chang, Jinzhan
Graphical abstract: Highlights: The onset condition equation is derived using the linear network method. The onset features and its impact factors are analyzed in detail. The steady-operation acoustic field features and working performances are predicted using DeltaEC code. Abstract: This paper mainly discusses the onset and steady-operation features of low temperature differential multi-stage traveling wave thermoacoustic engines. The onset condition is firstly derived based on the linear network model of a four-stage thermoacoustic engine. Then, the impacts of the mean pressure, working substance, hydraulic radius of regenerator, and stage number of this thermoacoustic engine are investigated in detail on the onset temperature and self-excited oscillation frequency by applying the network model for multi-stage systems. The steady-operation features, typically the acoustic fields and performances of this multi-stage traveling wave thermoacoustic engine are also discussed in this paper. Simulation results are compared to the published experimental data in the open literature domain and showed a good agreement.